2011
DOI: 10.1007/s10535-011-0025-7
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of rice hexokinase (OsHXK) family members in the mesophyll protoplasts of tobacco

Abstract: Hexokinase (HXK, EC 2.7.1.1) plays an important role in the metabolism and glucose signalling. To examine the characteristics of HXK gene family in rice, the subcellular localizations of ten hexokinases (OsHXK1 -OsHXK10) were determined using OsHXK::GFP fusion proteins in tobacco mesophyll protoplasts. As was previously demonstrated, OsHXK4 was detected in the chloroplast stroma, OsHXK5 and OsHXK6 in the mitochondria, and OsHXK7 and OsHXK10 in the cytoplasm. In the present study, OsHXKs were clearly divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…2c and Additional file 1: Table S3). Similar results were obtained for the cytosolic HXKs of rice, OsHXK7 and OsHXK8 [12, 37], suggesting that ZmHXK7 and ZmHXK8 could be in the cytosol. This is possible even if the TargetP 1.1 software [35] predicted that ZmHXK8 was located at the chloroplast.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…2c and Additional file 1: Table S3). Similar results were obtained for the cytosolic HXKs of rice, OsHXK7 and OsHXK8 [12, 37], suggesting that ZmHXK7 and ZmHXK8 could be in the cytosol. This is possible even if the TargetP 1.1 software [35] predicted that ZmHXK8 was located at the chloroplast.…”
Section: Resultssupporting
confidence: 81%
“…There are no chloroplast or Golgi HXKs as suggested before [9, 26], the localization analysis on protoplast corroborates the phylogenetic analysis, in which only dicot plants have plastid HXK (Additional file 1: Figure S1). The absence of a chloroplast HXK (type A HXKs) in maize suggests that Glc is phosphorylated by cytosolic isoenzymes and used in starch and fatty acid synthesis when night-time energy supply is limited in the chloroplast [24, 37, 4851]. However, it was also suggested that type A HXKs are only expressed in plants that tend to accumulate starch, which is not the case in maize [25, 52].…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analysis of mitochondrial proteins has located Arabidopsis AtHXK1 and AtHXK2 enzymes on the outside of the mitochondrial membrane (Giege et al, 2003; Heazlewood et al, 2004). Studies based on the use of GFP fusion proteins have shown that Arabidopsis AtHXK1 and AtHXK2, tomato SlHXK1, 2, and 3, Nicotiana benthamiana NbHXK1, rice OsHXK 2, 3, 5, 6, and 9, Sorghum SbHXK3, Populus trichocarpa PtHXK1, and spinach ( Spinacia oleracea ) SoHXK1 are associated with mitochondria (Cho et al, 2006a; Damari-Weissler et al, 2006, 2007; Kandel-Kfir et al, 2006; Kim et al, 2006; Balasubramanian et al, 2007; Karve et al, 2008, 2010; Cheng et al, 2011). Deletion of the putative N-terminal membrane anchor domains of the Arabidopsis AtHXK1, tomato SlHXK 1, 2, and 3, and the N. benthamiana NbHXK1 proteins resulted in their localization to the cytosol, confirming that this domain is a membrane anchor domain (Damari-Weissler et al, 2006; Kim et al, 2006; Balasubramanian et al, 2007).…”
Section: Intracellular Localization Of Hxks and Frksmentioning
confidence: 99%
“…However, cytosolic HXK were also identified in monocots. Four of the 10 rice HXKs, OsHXK1, OsHXK7, OsHXK8, and OsHXK10 lack or have a truncated N-terminal membrane anchor domain and are located in the cytosol (Cho et al, 2006a; Cheng et al, 2011). Cheng et al (2011) suggested that OsHXK1, OsHXK7, and OsHXK8 are also located within nuclei.…”
Section: Intracellular Localization Of Hxks and Frksmentioning
confidence: 99%
“…Additionally, most pathogenicities are related to gene function in the cell membrane, cytosol, and nucleus, suggesting that the localization of the protein is also an important factor for gene function. Similarly, rice hexokinase 10 (OsHXK10), a key player in sugar signaling and metabolism, has been shown to be differentially localized in the cytoplasm and mitochondria in a tobacco expression system [53] , [54] . Other members of HXK, OsHXK5 and OsHXK6 have recently been reported to retain a dual targeting ability for the mitochondria and the nucleus and to function as part of a glucose sensor in the cell [55] .…”
Section: Discussionmentioning
confidence: 99%